Safety and Modulatory Effects of Humanized Galacto-Oligosaccharides on the Gut Microbiome - Arnold, Jason W.; Whittington, Hunter D.; Dagher, Suzanne F.; Roach, Jeffery; Azcarate-Peril, M. Andrea; Bruno-Barcena, Jose M. (Frontiers in Nutrition, 2021)
Complex dietary carbohydrate structures including β(1-4) galacto-oligosaccharides (GOS) are resistant to digestion in the upper gastrointestinal tract and arrive intact to the colon where they benefit the host by selectively stimulating microbial growth. Studies have reported the beneficial impact of GOS (alone or in combination with other prebiotics) by serving as metabolic substrates for modulating the assembly of the infant gut microbiome while reducing GI infections. N-Acetyl-D-lactosamine (LacNAc, Galβ1,4GlcNAc) is found in breast milk as a free disaccharide and in human milk oligosaccharides (HMOs), which are composed of repeating and variably branched lactose and/or LacNAc units, often attached to sialic acid and fucose monosaccharides. Human glycosyl-hydrolases don’t degrade most HMOs, indicating that these structures have evolved as natural prebiotics to drive proper assembly of healthy infant gut microbiota. Despite its recognized biological significance, comprehensive studies to determine the impact and safety of LacNAc-containing oligosaccharides on the gut microbiome are lacking. Here, we sought to develop a novel enzymatic method for generation of LacNAc-enriched GOS, referred to herein as humanized GOS (hGOS). Humanized GOS is chemically distinct from HMOs and its effects in vivo have yet to be determined. Thus, we sought to evaluate its safety in 6-week-old C57BL/6J mice and demonstrate the prebiotic’s ability to modulate the gut microbiome. We first evaluated the efficiency of a Komagataella (Pichia) pastoris cell line carrying the membrane-bound β-hexosyl transferase (rBHT) from Hamamotoa (Sporobolomyces) singularis to generate GOS and hGOS from lactose and N-Acetyl-glucosamine (GlcNAc). The enzyme catalyzed the regioselective, repeated addition of galactose from lactose to GlcNAc forming the β-galactosyl linkage at the 4-position of GlcNAc and at the 1-position of D-galactose generating, in addition to GOS, LacNAc, and Galactosyl-LacNAc trisaccharides produced by sequential transgalactosylations. Longitudinal analysis of gut microbiome composition in stool samples collected from mice fed a diet containing hGOS showed transient diversity reductions. Differences in microbiome community composition mostly within Firmicutes were observed between hGOS and GOS, compared to control-fed animals. Together, our results signal that hGOS lacks adverse effects and it is able to modulate the gut microbiome in vivo, promoting growth of beneficial microorganisms including Bifidobacterium and Akkermansia.